2018
DOI: 10.1186/s12913-018-3105-y
|View full text |Cite
|
Sign up to set email alerts
|

Accepting telemedicine in a circulatory medicine ward in major hospitals in South Korea: patients’ and health professionals’ perception of real-time electrocardiogram monitoring

Abstract: BackgroundSouth Korean government is currently in progress of expanding the coverage of telemedicine projects as part of an attempt to vitalize service industry, but is facing fierce opposition from KMA. Practice of telemedicine requires sufficient discussions among related parties. Although the participation of medical specialists is important, agreement from the public is essential.MethodsThree main tertiary care centers in Seoul were selected for data collection. A total of 224 patients (patients n = 180, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“… 14 Additionally, another study suggested that, by providing a good experience with telehealth, we can enhance acceptance. 17 The accordance of telehealth acceptance between those with or without a chronic disease in our study may be due to the increasing demands on the health care systems to provide new innovative methods of health care provision to all patients. 5 …”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“… 14 Additionally, another study suggested that, by providing a good experience with telehealth, we can enhance acceptance. 17 The accordance of telehealth acceptance between those with or without a chronic disease in our study may be due to the increasing demands on the health care systems to provide new innovative methods of health care provision to all patients. 5 …”
Section: Discussionmentioning
confidence: 79%
“…Unlike Holtz and Lee et al ., this study showed no association between technology perceived ease of use and telehealth acceptance. 14 , 17 This could be attributed to the fact that almost all our participants were young with a median age of 26, who tend to use internet-connected devices or video calls in their daily life activities, such as e-learning and socializing platforms. However, a study stated that those who experienced telehealth before had different reasons to accept such technology from new users.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations